2020
DOI: 10.1039/d0sc04850j
|View full text |Cite
|
Sign up to set email alerts
|

Persistent, highly localized, and tunable [4]helicene radicals

Abstract: We report a series of tunable and persistent [4]-helicene neutral radicals by chemical reduction of the [4]-helicenium cation analogue. EPR spectroscopy and DFT calculations indicate that the unpaired electron is localized at the central carbon atom.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 52 publications
(80 reference statements)
2
26
0
Order By: Relevance
“…We also reduced 9‐mesityl‐10‐methylacridinium ([ 2 ] + ), known as Fukuzumi's photoredox catalyst, [2a] to generate 2 . , a radical whose stability is reminiscent of that recently described for related dimethoxyquinacridinyl radicals [13] . This radical, the structure of which was confirmed by X‐ray analysis, [14] features an EPR spectrum analogous to that of 1 .…”
Section: Figuresupporting
confidence: 53%
“…We also reduced 9‐mesityl‐10‐methylacridinium ([ 2 ] + ), known as Fukuzumi's photoredox catalyst, [2a] to generate 2 . , a radical whose stability is reminiscent of that recently described for related dimethoxyquinacridinyl radicals [13] . This radical, the structure of which was confirmed by X‐ray analysis, [14] features an EPR spectrum analogous to that of 1 .…”
Section: Figuresupporting
confidence: 53%
“…24 Similarly, our group recently reported the chemical reduction of a series of these cations leading to the isolation and characterization of the corresponding neutral radical analog (DMQA • ). 25 We also demonstrated that the helicene [ n Pr-DMQA][BF 4 ] salt (C + , Figure 2a) is an efficient photocatalyst undergoing both chemical reduction and oxidation reactions via single-electron transfer. 26 Yet, the use of these redox-active compounds has never been reported in electrochemical and energy storage applications.…”
mentioning
confidence: 77%
“…The one-electron process at E1/2 Red2 = -1.67 V is attributed to the NO2 C • / NO2 C ••transformation. 41,46 Upon scanning toward the cathodic region, a one-electron oxidation wave is observed at E1/2 Ox = 1.35 V, which is assigned to the NO2 C •++ / NO2 C + redox couple, and was 310 mV higher than the…”
Section: Electrochemical Studiesmentioning
confidence: 98%